Early numeracy skills in early childhood: the effect of numbered heads together cooperative learning methods - Warmansyah, Jhoni; Sabri, Ahmad; Nasution, Maifatma; Amalina, Amalina; Safna, Aisyah; Fitri, Amelia (SAINTIS Publishing, 2022)
This study aims to determine the effect of the cooperative learning method with the Numbered Heads Together type on numeracy skills in early childhood. This study used the pre-experimental method with a one group pretest-posttest design. The research sample for children aged 5-6 years was 16 children. Data collection was in the form of a checklist of child development data with value categories from not yet developed to very well developed. Data analysis used the t-test by fulfilling normality and homogeneity first. The results showed that the t-count value is greater than the t-table value (t-count t-table). So, it can be concluded that the cooperative learning method with the Numbered Heads Together type has an influence on the development of early childhood numeracy skills. Thus, the teacher can apply various types of cooperative learning methods in the classroom to improve other aspects of development.